Sikap Guru terhadap Peserta Didik dalam Belajar - Rici Kardo; Yuzarion Yuzarion (Faculty of Education Universitas Negeri Malang, 2017)
Abstract: This research is motivated by the phenomenon of attitudes of teachers towards learners. The sample this research is 314 students of Senior High School Malang City (SMAN Malang). This research use design ex-pos-facto. Data collected instruments attitudes of teachers towards learners valid and reliable. Results of the study, according to empirical findings teacher perceptions of learners have support learning, it is illustrated by the attitude: (1) teachers matter in the learning process and has shown kindness; (2) the teacher has a good share of responsibility; (3) a teacher sensitive to accept the diversity of learners; (4) the teacher can improve instruction in learning; and (5) the teacher has been able to pushing with both the creativity of learners. Abstrak: Penelitian ini dilatarbelakangi oleh fenomena sikap guru terhadap peserta didik. Sampel penelitian ini adalah 314 siswa SMAN Kota Malang. Jenis penelitiannya adalah penelitian ex-pos-facto. Data dikumpul dengan instrumen sikap guru terhadap peserta didik valid dan reliabel. Hasil penelitian, temuan empiris guru menurut persepsi peserta didik telah mendukung proses belajar, hal ini tergambar dari sikap: (1) guru peduli dalam proses belajar dan menunjukkan kebaikan; (2) guru telah berbagi tanggung jawab dengan baik; (3) guru sensitif menerima keragaman peserta didik; (4) guru dapat meningkatkan instruksi dalam belajar; dan (5) guru telah dapat mendorong dengan baik kreativitas peserta didik.